Hydrochemical Formation Mechanisms and Quality Assessment of Groundwater with Improved TOPSIS Method in Pengyang County Northwest China. Issue 3 (2011) - Peiyue, Li; Hui, Qian; Jianhua, Wu
Abstract : Inverse geochemical modeling was used in this paper to quantitatively study the formation mechanisms of groundwater in Pengyang County, China. An improved TOPSIS method based on entropy weight was used to perform groundwater quality assessment in this area. The assessment results show that the groundwater in the study area is fit for human consumption and the high concentrations of some elements can be attributed to the strong water-rock interactions. The inverse geochemical modeling reveals that the dominant reactions in different parts of the study area are different. In the south part of the study area, the precipitation of sodium montmorillonite, calcite and the dissolution of gypsum, fluorite, halite, albite and dolomite as well as CO2 dissolution and cation exchange are the major water-rock interactions, while in the north part, the leading reactions are the precipitation of gypsum, dolomite, sodium montmorillonite, fluorite, the dissolution of calcite and albite and the CO2 emission and cation exchange are also important. All these reactions are influenced by the initial aquatic environment and hydrodynamic conditions of the flow path.